Aerosol particle dry deposition velocity above natural surfaces: Quantification according to the particles diameter. (December 2017) - Pellerin, G.; Maro, D.; Damay, P.; Gehin, E.; Connan, O.; Laguionie, P.; Hébert, D.; Solier, L.; Boulaud, D.; Lamaud, E.; Charrier, X.
Abstract: To assess the impact of an accidental or chronic radionuclide release in form of aerosol particles in the atmosphere, it is important to study their dry deposition in a rural environment. For particles of less than 1 µm, there is a lack of experimental data in this regard, leading to uncertainty in terms of the results of models, which can reach up to two orders of magnitude (Petroff Mailliat, Amielh, & Anselmet, 2008). Moreover, there is no in situ deposition velocity measurement data available for particles that are smaller than 10 nm. The objective of this study is to measure and analyse the dry deposition velocity for aerosol particles with a particle size of between 2.5 nm and 1.2 µm, with particular focus on the particle size range of 2.5–14 nm. To this end, an in situ experimental method based on eddy correlation was used. This method uses an Electrical Low Pressure Impactor (ELPI, DEKATI) for particles of between 7 nm and 1.2 µm and an original method that entails coupling two condensation particle counters (CPC 3788 and 3786, TSI). Seven experimental campaigns were conducted between 2007 and 2015, during which the dry deposition velocities ( Vd in m.s −1 ) were obtained for atmospheric aerosol particles of size between 2.5 nm and 1.2 µm in size, above different natural surfaces (maize, grassland, bare soil and forest). The findings highlight the influence of the following parameters: friction velocity of the wind, surface sensible heat flux and atmospheric stability (quantified by the length of Monin-Obukhov). Comparing the findings for each natural surface revealed it can reasonably be assumed that the influence of each natural surface on deposition is mainly explained in the data provided by friction velocity ( u* m.s −1 ). The other parameters related to the natural surface, such as the Leaf Area Index (LAI) or vegetation cover properties (adherence, micro roughness), have a second order impact on all the findings. Highlights: Dry deposition velocities of aerosol particles between 2.5 nm and 1.2 µm by eddy correlation with a cospectral analysis. Seven experimental campaigns between 2007 and 2015 above different natural areas: maize, bare soil, grassland and forest. Emission phenomenon physically validated and correlate with the particles diameter. First dry deposition velocities of ultrafine particles (<10 nm) above natural surfaces. Correlation between the dry deposition velocities and the micrometeorological parameters U* and H .